Effects of ultrafiltration on Co-Metal Organic Framework/pre-hydrolysis solution carbon materials for supercapacitor energy storage - Li, Changwei; Sha, Lei; Yang, Kang; Kong, Fangong; Li, Peng; Tao, Yubo; Zhao, Xin; Chen, Honglei (Frontiers in Chemistry, 2022)
Here, a Co-Metal Organic Framework/pre-hydrolysis (Co-MOF/pre-hydrolysis) solution carbon material is prepared by a mild and environmentally-friendly hydrothermal carbonization technique using a pulping pre-hydrolysis solution as the raw material and Co-MOF as the metal dopant. The stable hollow structure provide sufficient space for particle shrinkage and expansion, while the low density and large specific surface area of the long, hairy tentacle structure provide a greater contact area for ions, which shorten the transmission path of electrons and charges. The materials exhibite excellent specific capacitance (400 F/g, 0.5 A/g) and stability (90%, 10000 cycles). The Change of different concentration ratios in the structures significantly affecte the electrochemical performance. The specific surface area of the carbon materials prepared by ultra-filtration increased, but the specific surface area decrease as ultrafiltration concentration increase. The specific capacitance decrease from 336 F/g for C-ZIF-67-1/3 volume ultrafiltration to 258 F/g for C-ZIF-67-1/5 ultrafiltration. The results indicate that energy storage by the carbon materials relied on a synergistic effect between their microporous and mesoporous structures. The micropores provide storage space for the transmission of ions, while the mesopores provide ion transport channels. The separation of large and small molecules after ultrafiltration concentration limite the ion transmission and energy storage of the pores.